2009
DOI: 10.1002/glia.20850
|View full text |Cite
|
Sign up to set email alerts
|

Imaging glioma cell invasion in vivo reveals mechanisms of dissemination and peritumoral angiogenesis

Abstract: Infiltration of cancer cells into normal tissue is a hallmark of malignant gliomas and compromises treatment options. A lack of appropriate models limits the study of this invasion in vivo, which makes it difficult to fully understand its anatomy and the role of dynamic interactions with structures of the normal brain. We developed a novel methodology by utilizing multiphoton laser scanning microscopy (MPLSM) to image the movement of glioma cells deep within the normal brain of live mice in real time. This all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
164
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 34 publications
19
164
1
1
Order By: Relevance
“…(b) Semiquantitative visual analysis of spheroid infiltration after 42 h (day 2) of confrontation under the above described conditions allows for noninvasive serial detection of brain tumors and metastasis on a cellular resolution in vivo. 23,24 Using this experimental approach, we now showed hMSC tropism toward experimental glioma in mice, which is in accordance to previous results. 5 Importantly, pretreatment of hMSCs with TNF-a potentiates the glioma-specific recruitment of hMSCs applied by intravenous injection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(b) Semiquantitative visual analysis of spheroid infiltration after 42 h (day 2) of confrontation under the above described conditions allows for noninvasive serial detection of brain tumors and metastasis on a cellular resolution in vivo. 23,24 Using this experimental approach, we now showed hMSC tropism toward experimental glioma in mice, which is in accordance to previous results. 5 Importantly, pretreatment of hMSCs with TNF-a potentiates the glioma-specific recruitment of hMSCs applied by intravenous injection.…”
Section: Discussionsupporting
confidence: 91%
“…To address this, we compared the extent with which hMSCs and hMSCs preincubated with TNF-a were able to selectively integrate into intracranial human glioma xenografts in nude mice using a chronic cranial window and in vivo multiphoton laser scanning microscopy (MPLSM). 23,24 Microscopic images of representative tumor regions acquired 24 h after intravenous injection of quantum dot-labeled hMSCs revealed that hMSCs had infiltrated the growing glioma (Figure 6a). Importantly, preincubation with TNF-a massively increased the number of hMSCs recruited to the tumor (Figure 6b).…”
Section: Microarraymentioning
confidence: 99%
“…33 This could be of relevance for analysis of stem cell populations that reside in defined anatomical spaces (e.g., as defined by hypoxia or vascular proximity), thereby enabling evaluation of their functional properties in their anatomical context. 34,35 Taken together, we have demonstrated that optical barcoding is a powerful tool that allows identification, quantification, tracking, and sorting of clonal subpopulations, as well as their functional assessment in vitro and in vivo. Complex heterogeneous systems are the result of the expansion of specific subpopulations driven by endogenous growth advantages, signaling networks, and selective pressure of the microenvironment.…”
Section: Discussionmentioning
confidence: 88%
“…Despite these observations, however, up to now there is no suitable in vivo/in vitro model available to directly visualize glial reactions during cerebral metastasis formation, in particular by bright field microscopy. Recent in vivo live imaging of carcinoma cells demonstrated their cerebral colonization behavior 8 . However, this method is very laborious, costly and technically complex.…”
mentioning
confidence: 99%
“…Furthermore, in vivo imaging is thus far limited to the visualization of the carcinoma cells, whereas interactions with resident cells have not yet been illustrated. Finally, investigations of human carcinoma cells within immunocompetent animals are impossible 8 .…”
mentioning
confidence: 99%